Integrating Environmental Cost Accounting with Sustainable Management for Impact Assessment - Ahmed, Ali Ibrahim; Obaid, Siham Abd Ali; Majeed, Yahya; Khattab, Huda Yousif (Journal of Ecohumanism, 2024)
Background: The negative environmental consequences generated by building material production firms, particularly medium and large-scale ones in Vietnam, have highlighted the importance of good environmental management accounting (EMA) methods. Objective: The articles aim to investigate the factors that influence EMA use in the building material sector and the relationship between EMA procedures and financial and environmental performance efficiency. Methodology: Between 2018 and 2019, a survey of chief management accountants from 600 Vietnamese building material businesses yielded 418 valid replies. The data was analyzed using SPSS 22.0 software. Results: The article identifies six key factors that positively influence EMA implementation: government enforcement, stakeholder interest, positive environmental strategies, community expectations, professional education network, and financial condition, with government enforcement having the most significant impact. Furthermore, it was discovered that EMA adoption considerably improves both financial and environmental efficiencies, supporting the concept that environmental efficiency contributes to financial success. Conclusion: The findings highlight the importance of government policies and stakeholder interests in encouraging EMA practices among building material firms. Implementing EMA helps achieve environmental sustainability and improves financial performance, indicating that eco-friendly policies benefit both the earth and corporate profitability.